SUPPLY CHAIN MANAGEMENT PERFORMANCE OF ORGANIC RICE IN PRINGSEWU REGENCY - Sri Handayani; Muhammad Irfan Affandi (AIBPM Publisher, 2019)
The problem of organic rice farming is the limitation of market information. Organic rice products can’t be sold at high prices, some are still sold by farmers at nonorganic prices. Organic rice supply chain networks need to be identified by farmers so that farmers have market information and supply chain performance. For this reason, this research purpose to analyze the supply chain of organic rice in Pringsewu Regency. Data analysis method uses the concept of supply chain management performance with the Supply Chain Operations Reference (SCOR) approach. SCOR consists of four elements including reliability, responsiveness, flexibility, and assets. The results of measuring the performance of organic rice supply chains at all levels in the attributes of responsiveness and flexibility have achieved the superior performance position. The performance of organic rice supply chains attributes of asset at the farm level only achieves an advantage. But the supply chain performance in the attribute of reliability has not been able to reach a good performance position. So there needs to be an improvement effort through disciplinary shipping arrangements and product quality improvements to improve supply chain performance.